Coordinated Dispersion and Aggregation of Gold Nanorod in Aptamer-Mediated Gestational Hypertension Analysis - Bao, Xiucui; Huo, Gaoxiang; Li, Li; Cao, Xuebin; Liu, Yamei; Lakshmipriya, Thangavel; Chen, Yeng; Hariri, Firdaus; Gopinath, Subash Chandra Bose (Hindawi, 2019)
Gestational hypertension is one of the complicated disorders during pregnancy; it causes the significant risks, such as placental abruption, neonatal deaths, and maternal deaths. Hypertension is also responsible for the metabolic and cardiovascular issues to the mother after the years of pregnancy. Identifying and treating gestational hypertension during pregnancy by a suitable biomarker is mandatory for the healthy mother and foetus development. Cortisol has been found as a steroid hormone that is secreted by the adrenal gland and plays a pivotal role in gestational hypertension. A normal circulating level of cortisol is involved in the regulation of blood pressure, and it is necessary to monitor the changes in the level of cortisol during pregnancy. In this work, aptamer-based colorimetric assay is demonstrated as a model with gold nanorod to quantify the level of cortisol using the coordinated aggregation (at 500 mM of NaCl) and dispersion (with 10 mu M of aptamer), evidenced by the scanning electron microscopy observation and UV-visible spectroscopy analysis. This colorimetric assay is an easier visual detection and reached the limit of detection of cortisol at 0.25 mg/mL. This method is reliable to identify the condition of gestational hypertension during the pregnancy period.